Weighting method for modal parameter based damage detection algorithms - Fayyadh, M.M.; Abdul Razak, H. (2011)
When researchers use bending modes for the purpose of damage detection, a number of available modes are adopted, each of which return a value indicating the severity of damage. Normally, there is a variance in the sensitivity of different modes and the global stiffness change is derived by taking the algebraic average, which is equivalent to the mean in statistical analysis terms. This study proposes weighting method for damage detection algorithms based on the bending mode shapes for beam structures. The results of the proposed reliability weighting method for two damage severity algorithms are presented, that is, one based on the natural frequencies and the other based on the mode shape vectors.